Revenue in Service Quality Perspective at A Traditional Coffee Shop in Balongpanggang Village - Khoirotul Ummah; Rahmat Agus Santoso (Universitas Muhammadiyah Gresik, 2023)
ABSTRACT This study aims to analyze the income description of traditional coffee shops in Balongpanggang Village through 5 dimensions of service quality dslsm facing cafes in Balongpanggang sub-district. By collecting data from 5 informants and 1 key informant as the opening of the research to find accurate results. The presentation of the data is done using data analysis, namely data reduction, data display and conclusions. The results of this study found that the income earned by paying attention to the tangible dimension was caused by the cleanliness and tidiness of the coffee shop. Earnings income by taking into account the dimension of reliability is caused by the application of careful and fast services. Earnings revenue by paying attention to the dimension of responsiveness caused by customer requests and notifications. Earnings income by paying attention to the assurance dimension is caused by inspection of goods, price stability, honesty, courtesy and patience. Earning income by paying attention to the empathy dimension is caused by greeting, joking, tolerance and incentives.